2023
DOI: 10.1002/ehf2.14404
|View full text |Cite
|
Sign up to set email alerts
|

Activating transcription factor 4 drives the progression of diabetic cardiac fibrosis

Abstract: Aims Diabetic cardiomyopathy (DC) is one of serious complications of diabetic patients. This study investigated the biological function of activating transcription factor 4 (ATF4) in DC. Methods and results Streptozotocin‐treated mice and high glucose (HG)‐exposed HL‐1 cells were used as the in vivo and in vitro models of DC. Myocardial infarction (MI) was induced by left coronary artery ligation in mice. Cardiac functional parameters were detected by echocardiography. Target molecule expression was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In addition to Tcf21, Arnt, Stat5a, and Stat5b, previous studies have explored and demonstrated the significant roles of other transcription factors in DCM. For instance, ATF4 [59] in DCM promotes cardiac fibrosis and oxidative stress, while downregulation of Bmal1 [60] induces mitochondrial dysfunction by promoting Bcl2/IP3Rmediated mitochondrial Ca 2+ overload, leading to diabetic cardiomyopathy. A recent study has also revealed that ketone bodies can rescue mitochondrial dysfunction through epigenetic remodeling [61].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Tcf21, Arnt, Stat5a, and Stat5b, previous studies have explored and demonstrated the significant roles of other transcription factors in DCM. For instance, ATF4 [59] in DCM promotes cardiac fibrosis and oxidative stress, while downregulation of Bmal1 [60] induces mitochondrial dysfunction by promoting Bcl2/IP3Rmediated mitochondrial Ca 2+ overload, leading to diabetic cardiomyopathy. A recent study has also revealed that ketone bodies can rescue mitochondrial dysfunction through epigenetic remodeling [61].…”
Section: Discussionmentioning
confidence: 99%
“…60 In a preclinical study conducted in in vivo and in vitro rodent models, transcription factor 4 (ATF4) was identified as a regulator of apoptosis and fibrosis. 61 Heart failure associated metabolic derangements develop not only in adults but also in children, 62 and these alterations are further aggravated by diabetic cardiomyopathy where metabolic alterations via dyslipidaemia and subsequent lipid-induced toxicity (i.e. lipotoxicity) harm and limit the function of the cardiovascular system.…”
Section: Preclinical and Translational Investigationsmentioning
confidence: 99%